Juridical Analysis of Human Rights Protection in the Era of Digital Transformation: Perspective of Laws and Regulations - Absor, Ajib Mudakirin (Indonesia Media Law Review, 2023)
Human Rights are inherent rights possessed by dignified human beings, bestowed upon them by God Almighty. These rights ensure the fundamental entitlements that humans naturally possess and cannot be separated from them. In life, individuals possess personal data that is inherent to their identities and should be safeguarded as their privacy. The Constitution of the Republic of Indonesia in 1945 established this principle, assigning the responsibility to the state to protect and enforce laws against violations and misuse of personal data. The ever-growing information and communication technology, driving the country towards digital transformation in various sectors, presents a complex challenge that necessitates comprehensive regulations and strict enforcement of laws concerning personal data protection. This study aims to examine the formulation of new regulations and their alignment with internationally applied rules and guidelines. The research methodology employed is juridical normative with a conceptual approach, aiming to elucidate the essence of personal data protection in Indonesia as a realization of human rights protection. It highlights the necessity of a dedicated authority or agency responsible for safeguarding and enforcing personal data protection in light of its numerous implications. The significance of Personal Data Protection arises from the advancement of increasingly sophisticated digitalization processes, necessitating specialized regulations to uphold citizens' human rights in the digital transformation era.